Designing Sustainable Transportation Strategy in Covid-19: Jabodetabek Commuter Community Movement in Indonesia - Muhammad Syahbandi; Andri N.R. Mardiah; Suryani Eka Wijaya (Amcolabora, 2022)
Sustainable transportation systems, especially environmentally friendly transportation systems, play an important role in improving quality of life in urban areas. Urban communities in many developing countries experienced air pollution that has exceeded the national ambient air quality standard threshold. This is due to the increase of motorized vehicles. In Indonesia, the high movement of the Jabodetabek urban community poses a high risk to the increased air pollution in urban areas. This research aims are to analyse and respond to the phenomenon of climate change in the transport sector, in particular by developing strategies for sustainable urban transportation systems. Using qualitative research, data is collected from in-depth interviews with transport experts and practitioners and NGOs activities in the transport sector. The findings of this research highlight the key elements for developing an environmentally friendly transportation system and its strategies in the Jabodetabek urban area that is appropriate and following the needs of the regional commuting community. urban Jabodetabek. By using the CA analysis method and SWOT analysis, the development of an environmentally friendly transportation system for the Jabodetabek urban area is the current urgency at least for all stakeholders and all elements of society to build commitment, and a common vision and mission in building a fully integrated and perfect national transportation system, and monitoring and evaluating the order of the transportation system and public services to date.